OFR-10-72 A Mathematical Model Simulating Flow Of Methane And Water In Coal ? Introduction - H. S. Price (The National Institute for Occupational Safety and Health (NIOSH), 2012)
This report discusses the development of a mathematical model that describes the flow of methane only and methane and water in a coal bed during mining operations. Because of the complex geometry, boundary conditions and fluid properties, the model is based on a numerical solution to the equations describing flow. The goals for the development of this model and requirements to which it complies are for the most part expressly stated in Request for Proposal No. 50110752. In addition to the capabilities specified under the scope of work the model can handle an anisotropic porous medium and a source term has been added which will simulate, somewhat, the effects of desorption. This term will be pressure dependent. The effect of time on such a term is only taken care of in the change of pressure with time. This source term will have the dimensions of Mcf/day/Mcf pore volume. It will be a part of the input data to be supplied by the user and will be entered as a table of rates versus pressure. These models consider the fracture system as the main porosity. All computed results pertain to the fractures. The source term mentioned above represents the flow from the matrix porosity into the fracture. Such flow should be small compared with the flow between fractures since these models handle only one porosity structure system.